Spatial Distribution and Contamination Assessment of Trace Metals in the Coral Reef Sediments of Kavaratti Island in Lakshadweep Archipelago, Indian Ocean. Issue 2 (17th February 2020) - Joy, Anu; Anoop, P P; Rajesh, R; Mathew, Angel; Gopinath, Anu
ABSTRACT: Surficial coral reef sediments collected from 17 sampling stations (shore, lagoons, and outer lagoons) of Kavaratti, Island belonging to Lakshadweep Archipelago were analyzed for trace metal concentration, total organic carbon and sediment grain size composition. The predominant grain size constituent of sediments from the sampling stations was medium sand with low organic carbon content. Except Cd and Pb, all the other trace metals selected for the study were below their global average shale concentration. The sediment contamination was assessed on the basis of geochemical and ecological risk indices. Considerable contamination and significantly high ecological risk were reported from all stations and the serious threat was from Cadmium. Diesel-based power generation, untreated sewage, activities related to shipping, fishing, agriculture, and tourism are the main anthropogenic sources contributing to trace metal pollution in Kavaratti. Statistical analysis of the data also supported the anthropogenic sources of origin of trace metals.